2014
DOI: 10.1523/jneurosci.4261-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Activity-Dependent Tau Protein Translocation to Excitatory Synapse Is Disrupted by Exposure to Amyloid-Beta Oligomers

Abstract: Tau is a microtubule-associated protein well known for its stabilization of microtubules in axons. Recently, it has emerged that tau participates in synaptic function as part of the molecular pathway leading to amyloid-beta (A␤)-driven synaptotoxicity in the context of Alzheimer's disease. Here, we report the implication of tau in the profound functional synaptic modification associated with synaptic plasticity. By exposing murine cultured cortical neurons to a pharmacological synaptic activation, we induced t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
205
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 216 publications
(220 citation statements)
references
References 48 publications
10
205
1
Order By: Relevance
“…The molecular basis for these alterations is unclear, but they are indicative of a redistribution of synaptic weights, which is consistent with the bidirectional effect of PSD size that we also observed in these neurons. In fact, Tau is present in dendritic spines (Ittner et al , 2010; Mondragon‐Rodriguez et al , 2012; Frandemiche et al , 2014). In these structures, it has been shown that activation of NMDA glutamate receptor triggers Tau phosphorylation, thus regulating the interaction of Tau with the actin cytoskeleton, PSD95, and Fyn kinase (Ittner et al , 2010; Mondragon‐Rodriguez et al , 2012; Frandemiche et al , 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular basis for these alterations is unclear, but they are indicative of a redistribution of synaptic weights, which is consistent with the bidirectional effect of PSD size that we also observed in these neurons. In fact, Tau is present in dendritic spines (Ittner et al , 2010; Mondragon‐Rodriguez et al , 2012; Frandemiche et al , 2014). In these structures, it has been shown that activation of NMDA glutamate receptor triggers Tau phosphorylation, thus regulating the interaction of Tau with the actin cytoskeleton, PSD95, and Fyn kinase (Ittner et al , 2010; Mondragon‐Rodriguez et al , 2012; Frandemiche et al , 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Tau is present in dendritic spines (Ittner et al , 2010; Mondragon‐Rodriguez et al , 2012; Frandemiche et al , 2014). In these structures, it has been shown that activation of NMDA glutamate receptor triggers Tau phosphorylation, thus regulating the interaction of Tau with the actin cytoskeleton, PSD95, and Fyn kinase (Ittner et al , 2010; Mondragon‐Rodriguez et al , 2012; Frandemiche et al , 2014). Interestingly, the basal subtle electrophysiological alterations described in this work seem to occur specifically in granule neurons, as it has been demonstrated that Tau deficiency does not affect basic synaptic currents in other regions of the brain (Ittner et al , 2010).…”
Section: Discussionmentioning
confidence: 99%
“…As discussed above, there is clear evidence for a physiological role of tau in synaptic plasticity (Frandemiche et al., 2014; Hu et al., 2011). Conversely, hyperphosphorylated tau accumulates in synaptic spines and alters synaptic function in a mouse model of AD (Hoover et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, hyperphosphorylated tau accumulates in synaptic spines and alters synaptic function in a mouse model of AD (Hoover et al., 2010). Consistent with this observation, tau translocates to synaptic spines in an activity‐dependent manner, an event blocked by Aβ (Frandemiche et al., 2014). Taken together, these data clearly indicate that tau can contribute to cognitive deficits both by toxic gain‐of‐function and by loss‐of‐function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation